An initial agent behaviour modelling and definition methodology as applied to unmanned aerial vehicle simulations. (18th December 2008) - Marsh, William E.; Hill, Raymond R.
In some agent-based modelling systems, it is difficult for domain-expert users to define and implement agent behaviours without possessing extensive programming knowledge. This research developed a process through which non-programmer, domain experts can effectively interact with a modelling environment to define, develop and implement agent-based behaviours. This paper presents a new methodology for the definition and implementation of UAV agent behaviours based on diagramming an agent's controller state and using diagram syntax to generate the executable algorithm. No programming knowledge is required to reuse modular behaviours and trigger. After describing the methodology, a sample scenario is presented as a proof-of-concept.